Analysis of Cassava Farming, Cimanggu Variety Case Study of Cassava Farmers in Jabung Village, Jabung District, East Lampung Regency - Ulinuhayani, M.; Singgih, Bambang; Rusdi, Nurul; Widodo, Yudi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The purpose of this study was to analyze the production costs of cassava farming, the income of cassava farming, and the feasibility of cassava farming in the study area. The research location was determined purposively based on the consideration that the studied area is one of the centers of cassava production of the Cimanggu variety for chips, which is a potential food ingredient in East Lampung Regency, but cassava grown locally by farmers still has low productivity. In order to increase cassava productivity and production, one of the farmers in Jabung Village, Jabung District, East Lampung Regency developed a superior cassava variety, the Cimanggu variety. This study aims to determine revenue, R/C ratio, and constraints of cassava farming of the Cimanggu variety by farmers in Jabung Village, Jabung District, East Lampung Regency. The results of our research using 2024–2025 data show production costs of Rp12,395,366.67 with revenue of Rp56,848,425.00; the results obtained are Rp44,453,058.33 per hectare with an R/C ratio of 3.59, which means that cassava farming is very profitable or feasible to be developed. The technical constraints faced are limited fertilizer, cassava seeds, and white pest attacks. The economic constraint is the low price of wet cassava tubers in the market.